Training for Sustainable Development: Assessing the Impact on Community Resilience Marketing - Hasyim, Hasyim; Bakri, Muhammad (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study assesses the impact of sustainable development training on community resilience marketing, focusing on enhancing participants' understanding of sustainability and its application in marketing strategies. Research Design and Methodology: A qualitative literature review method is employed, systematically gathering, evaluating, and synthesizing existing research on sustainable development training. The review critically examines academic sources to identify key themes and patterns related to the influence of training on marketing practices aimed at supporting community resilience. Findings and Discussion: The findings indicate that sustainable development training significantly enhances participants' knowledge of sustainability principles, leading to the adoption of green marketing, ethical advertising, and community-driven initiatives. These practices contribute to community resilience by addressing local environmental and social challenges and fostering local engagement. Training also promotes collaboration and knowledge sharing, creating networks that support continuous improvement and adaptation in marketing strategies. Implications: The study highlights social networks' transformative potential in enhancing community empowerment but underscores the necessity for targeted interventions to mitigate issues related to digital access, online safety, and the ethical use of data. These insights are valuable for policymakers, technology developers, and educators aiming to create inclusive digital environments that support community growth and individual empowerment.